SILALA: Population Administration Service Innovation in Aceh Singkil District - ikhsan, ikhsan; Asiah, Nur (Journal of Social Politics and Governance (JSPG), 2023)
This paper discusses the innovation of population administration services at the Aceh Singkil District Population and Civil Registration Service. The purpose of this study is to see how the development of population administration service innovations can provide good service to the community through the website based SILALA application. Data collection techniques through interviews with employees and the community using the SILALA application. The results show that the SILALA application has been well developed because it has complete features and can be used anywhere and anytime so that population administration services can be more effective and efficient. The conclusion from this study is that the innovation of population administration services has been going well even though the service is still constrained by an unstable network that sometimes disrupts population administration services.